Population cycles in voles and lemmings: state of the science and future directions. (10th May 2019) - Oli, Madan K.
Abstract: Despite nearly a century of research, the causes of population cycles in Arvicoline rodents (voles and lemmings) in northern latitudes are not yet fully understood. Theory tells us that delayed density‐dependent feedback mechanisms are essential for rodent population cycles, suggesting vegetation–rodent, rodent–parasite or rodent–predator interactions as the most likely drivers of population cycles. However, food provisioning, carried out either indirectly through fertilisation treatments of the habitat or directly through food supplementation, has failed to alter population cycles substantially, suggesting that variation in food supply by itself is not necessary or sufficient to cause cyclic fluctuations in abundance. Predator exclusion experiments conducted in Fennoscandia have succeeded in slowing population crashes and increasing autumn densities, implicating predation as the most likely cause of rodent cycles in this region. However, experimental removal of specialist predators in northern England had no discernible effect on a cyclic vole population, casting doubt on the notion that predation is a necessary explanation of rodent population cycles. Population cycle research has contributed substantially to our current understanding of the dynamics, regulation and persistence of biological populations, but we do not yet know with certainty what factors or processes cause multiannual population fluctuations or if population cycles are driven by the same mechanisms everywhere. Recent theoretical and empirical studies suggest that extrinsic factors (primarily food supply and predator abundance) may interact with population intrinsic processes (e.g. dispersal, social behaviour, stress response) to cause multiannual population fluctuations and to explain biological attributes of rodent population cycles. Solving the enigma of population cycles may necessitate identifying factors and processes that cause phase‐specific demographic changes and performing conclusive experiments to ascertain the mechanisms that generate multiannual density fluctuations. Abstract :